KONSTRUKSI MAKNA FASHION DALAM PENGGUNAAN MASKER DI INSTAGRAM - Iin Soraya; Mareta Puri Rahastine; Ganjar Wibowo (J-IKA : Jurnal Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas BSI Bandung, 2021)
In the era of covid 19 masks have become a necessity in activities, the obligation to use masks for daily use, this makes masks more and more stylish. One of the fashion styles that creates fashion masks is Gerry Yo. Gerry's fashion masks are regularly uploaded on social media, namely Instagram. The photos of masks uploaded to Gerry Yo's account are a symbol that masks with various fashion patterns, accessories and styles are different from masks in general. By using sequins even to the Swarovski stone. The purpose of this study is to describe the construction of the meaning of fashion in the use of masks on Instagram. The theory used in this research is the theory of social reality construction, the paradigm used is the constructivism paradigm. The method used is descriptive qualitative with analytical knife using triangle meaning semiotics Charles Sanders Pierce Semiotics. The result of the research is that the reality that you want to build on the @gerryyoheadpiece instagram account creates a new culture with masks as fashion, using masks is still trendy. Furthermore, it is objective about the depiction of women using masks but still beautiful. Externalization describes the use of masks that used to be considered for health but this time for glamorous fashion. The meaning built on Instagram @gerryyoheadpiece is that masks can now express high social class for a woman.